Scientific and technical cooperation between developing countries. Formation of middle-level auxiliary and technical health personnel (Educacion medica y salud, 1986)
Technical cooperation between developing countries is not easy in the absence of direct communication between them and of the requisite infrastructure. However, technical cooperation at this level is an important form of assistance to countries. The subject of the article is the technical assistance provided by Cuba to Nicaragua, with the collaboration of the Pan American Health Organization, to enable the Nicaraguan institutions to establish short-term health programs. The success of the cooperation was made possible by an effective concentration of resources in a limited field. After a brief preparatory stage in which the operational methodology was laid down and its phases were scheduled, functions were apportioned. The Ministry of Public Health of Cuba provided the directors and professionals for middle-level instruction in Nicaragua and collaborated in the study plans, the training of technicians and teaching staff, and the preparation of textbooks and manuals, while the Ministry of Health of Nicaragua provided food and lodging for the teaching staff and PAHO sponsored the meetings and workshops, provided education materials and prepared textbooks and manuals. The basic aim of the agreement was to facilitate the imparting of health knowledge to the least developed population areas. To accomplish this purpose, many activities were programmed that were almost completely carried out during that period.